Pengaruh Pengawasan terhadap Disiplin Kerja Karyawan pada Koperasi Margo Mulyo Ambulu, Kabupaten Jember - Meika, Intan; Pramono, Rudy Eko; Wahjuni, Sri (e-Sospol, 2017)
Abstract This research was aimed at probing the influence of monitoring on employees’ occupational discipline at Margo Mulyo Ambulu cooperation. Monitoring can be considered as an activity to determine and correct the important deviations from the results of planned activities. Therefore, companies are required to provide encouragement for employees to be more discipline. Discipline is a management action to encourage the company members to meet demands in accordance with the provisions. Carried out in quantitative explanatory approach, the research involved a number of data collection methods, comprising of observation, questionnaire, and library research. The instruments operationalized in the study denoted Likert-model scalar questionnaire, with several modifications operative. The data analysis technique applied in the study was linear regression analysis. The collected data were gathered using questionnaires, which were distributed to thirty employees involved as research sample. The research findings revealed significant influence exerted by monitoring on the employees’ occupational discipline at Margo Mulyo Ambulu cooperation. The data evinced that the variable under investigation, the influence of monitoring, counted for 70.5% of the employees’ occupational discipline, while 29.5% was under the influence of variables with which this research did not grapple.